Identity matters : John, the Jews and Jewishness - Hakola, Raimo. (Novum Testamentum, Supplements, 2005)
This book challenges current scholarly consensus concerning John's references to the Jews in two ways. First, the author suggests that John's portrayal of the Jews cannot be understood as a response to the violent policy of John's opponents. Second, the author claims that John's portrayal of Jewishness is much more ambivalent than is often claimed today. The first part of the book offers a detailed criticism on the so called two-level reading strategy which claims that John's references to the Jews emerge from the conflict with rabbinic Judaism. The second part examines in detail John's relationship to some basic markers of Jewishness. The book contributes to the ongoing discussion of anti-Judaism in John and efforts to understand John's historical setting.